Brucella spp. in the western North Pacific and Antarctic cetaceans: a review - Ohishi, Kazue; Fujise , Yoshihiro; Maruyama, Tadashi (J. Cetacean Res. Manage., 2023)
Brucella spp. has been reported in a variety of marine mammals worldwide. Serological and pathological studies were conducted on Brucella spp. in the western North Pacific using samples from three whale species collected during 2000 under the second phase of the Japanese Whale Research Program under Special Permit in the Western North Pacific (JARPN II). Serum samples from 40 common minke whales (Balaenoptera acutorostrata), 43 Bryde’s whales (B. edeni) and 4 sperm whales (Physeter macrocephalus) were assessed with agglutination testing designed for B. abortus detection. Brucella-specific serum antibodies were detected in 38% of common minke whale samples. A lower prevalence (9%) of the antibody was observed for the Bryde’s whale samples, whereas no specific antibody against Brucella was observed for the four sperm whales. Serum samples from 104 Antarctic minke whales (B. bonaerensis) collected under the Japanese Whale Research Program under Special Permit in the Antarctic (JARPA) were analysed, and no Brucella-specific antibodies were detected. Granular lesions with caseation and mineralisation were found in 35% (13 males and one female) of 40 minke whale gonads. Similar lesions were also observed in the gonads of one male and one female Bryde’s whale. These gonad lesions were not found in 440 Antarctic minke whales and five sperm whales, despite the thorough examination conducted for reproduction studies. Histopathological studies showed that the lesions consisted of epithelioid cells, multinucleated giant cells and had an infiltration of lymphocytes. DNA fragments were amplified by PCR using specific primers from ten of 22 abnormal testis tissues collected from common minke whales. The DNA sequences had IS711 transposable elements downstream of bp26, characteristic of marine strains of Brucella spp. The gene structure of omp2, and specific PCR products for seal strains, showed similarity to Atlantic seal strains rather than Atlantic whale strains. This showed that classification based on marine mammal host species, B. cetacea and B. pinippedia is not appropriate. Considering the zoonotic nature of the genus Brucella, the crews and researchers who have had frequent contact with whales were serologically examined and were found to have no health issues associated with this agent. No Brucella-specific antibody was detected in the sera from 51 persons examined in 2001, nor from 103 examined issues in 2003.